Multiple Functional Effects of RET Kinase Domain Sequence Variants in Hirschsprung Disease. Issue 1 (23rd August 2012) - Hyndman, Brandy D.; Gujral, Taranjit S.; Krieger, Jonathan R.; Cockburn, Jessica G.; Mulligan, Lois M.
<x xml:space="preserve">Abstract</x> The REarranged during Transfection (RET) gene encodes a receptor tyrosine kinase required for maturation of the enteric nervous system. RET sequence variants occur in the congenital abnormality Hirschsprung disease (HSCR), characterized by absence of ganglia in the intestinal tract. Although HSCR‐RET variants are predicted to inactivate RET, the molecular mechanisms of these events are not well characterized. Using structure‐based models of RET, we predicted the molecular consequences of 23 HSCR‐associated missense variants and how they lead to receptor dysfunction. We validated our predictions in biochemical and cell‐based assays to explore mutational effects on RET protein functions. We found a minority of HSCR‐RET variants abrogated RET kinase function, while the remaining mutants were phosphorylated and transduced intracellular signals. HSCR‐RET sequence variants also impacted on maturation, stability, and degradation of RET proteins. We showed that each variant conferred a unique combination of effects that together impaired RET protein activity. However, all tested variants impaired RET‐mediated cellular functions, including cell transformation and migration. Our data indicate that the molecular mechanisms of impaired RET function in HSCR are highly variable. Although a subset of variants cause loss of RET kinase activity and downstream signaling, enzymatic inactivation is not the sole mechanism at play in HSCR.